Mastitis pattern analysis: epidemiology into practice. (2nd September 2022) - Breen, James; Manning, Al
Abstract : Analysis of data to inform decision making in dairy animal practice is a cornerstone of modern dairy herd health work and is routinely carried out in areas such as fertility management and mastitis control. Mastitis in dairy herds continues to be important and relevant to veterinary advisors for many reasons, such as cow welfare, the cost of disease, the use of antimicrobials and the sustainability of farming and food supply, including environmental impact and waste milk. When implementing control measures to reduce mastitis infection rates on farm, herd level analysis of infection 'patterns' to inform decision making has been shown to be an important first step. Feedback from participants using the Agriculture and Horticulture Development Board (AHDB) Dairy Mastitis Control Plan previously indicated that the first stage of the Plan, analysing patterns and making a herd 'diagnosis', was often a difficult stage for Plan deliverers. The new AHDB Dairy QuarterPRO scheme offers an 'entry-level' method of routinely monitoring mastitis on farm and builds in a rapid method of assessing the predominant mastitis infection patterns present on farm, using somatic cell count and clinical mastitis records. A new fully automated mastitis pattern analysis report is now available to all milk recording dairy herds in the UK through their milk recording organisation, allowing routine assessment of the predominant pattern of infection, and enabling farmers and veterinary surgeons to highlight the most important area on their farm for mastitis control.